Inorganic pigments - Pfaff, Gerhard (De Gruyter textbook)
"The book provides a complete overview on inorganic pigments and their use in dye industry. Each chapter introduces a certain class of pigment in respect of fundamentals, manufacture, properties and toxicology and thus being very valuable for paint chemists and materials specialists. The readers will benefit from a concise and well-structured text, numerous examples and a set of test questions in the end of each chapter. A comprehensive overview of all main types of inorganic pigments. Each chapter has a uniform structure based on a certain type of pigment. A set of questions is provided in the end of each chapter to test the understanding of the content."